2016
DOI: 10.1021/acs.cgd.6b00110
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Spectroscopic Studies and First-Principles Investigations of the Zinc Vacancy Mediated Ferromagnetism in Mn-Doped ZnO Nanoparticles

Abstract: A systematic study on the room temperature ferromagnetism (RTFM) in undoped and Mn-doped ZnO nanoparticles (NPs) prepared by the coprecipitation method has been reported. The neutral and singly ionized zinc vacancy defects exhibited in the results of photoluminescence (PL), micro-Raman spectroscopy, and electron paramagnetic resonance (EPR) studies are found to be of ferromagnetic origin in bare ZnO, and it has been confirmed that Mn2+ ions substitutionally enter at Zn2+ sites in wurtzite ZnO. The results of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 68 publications
2
13
0
Order By: Relevance
“…Undoped and doped ZnO NPs of different shapes were reported to demonstrate significant emission changes, depending on capping molecules and solvents used. , The PL spectra of MZO-16 (dendrites) and MZO-18 (pyramid dimers) display three bands at ∼412, 435, and 464 (shoulder) nm, while the spectra of other samples show a broad peak with a maximum at ∼425 nm. The presence of three emission bands in the 400–500 nm range shows that defect states are introduced at several discrete energies within the band gap. , For elongated samples (MZO-1, MZO-3, and MZO-8), the defect states are partially quenched, which is reflected in featureless peaks with lower intensities. This allows us to conclude that PL properties are shape-dependent for the Mn-doped ZnO NPs discussed in this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Undoped and doped ZnO NPs of different shapes were reported to demonstrate significant emission changes, depending on capping molecules and solvents used. , The PL spectra of MZO-16 (dendrites) and MZO-18 (pyramid dimers) display three bands at ∼412, 435, and 464 (shoulder) nm, while the spectra of other samples show a broad peak with a maximum at ∼425 nm. The presence of three emission bands in the 400–500 nm range shows that defect states are introduced at several discrete energies within the band gap. , For elongated samples (MZO-1, MZO-3, and MZO-8), the defect states are partially quenched, which is reflected in featureless peaks with lower intensities. This allows us to conclude that PL properties are shape-dependent for the Mn-doped ZnO NPs discussed in this work.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of three emission bands in the 400− 500 nm range shows that defect states are introduced at several discrete energies within the band gap. 56,61 For elongated samples (MZO-1, MZO-3, and MZO-8), the defect states are partially quenched, which is reflected in featureless peaks with lower intensities. This allows us to conclude that PL properties are shape-dependent for the Mn-doped ZnO NPs discussed in this work.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Pal et al [38] showed that ferromagnetic behavior depends on many parameters, including the concentration and distribution type of transition metal ions, defect concentration, n-type doping, p-type doping, and particle morphology. Ponnusamy et al [53] believed that Zn vacancy (V Zn ) and bound magnetic polaron formed by nearby Mn 2+ interacted to form high-saturated magnetic intensity. Some people believe that the ferromagnetism behavior is attributed to the formation of some nanoscale nickel-related secondary phases, such as Ni precipitation and NiO.…”
Section: Resultsmentioning
confidence: 99%
“…The results show that the doped systemis FM, and the Curie temperature can reach above room temperature. Ponnusamy et al [14] used first-principles to study the magnetic effect mediated by Zn vacancies in Mn-doped ZnO. The results show that the ferromagnetism in undoped ZnO originates from V Zn .…”
Section: Introductionmentioning
confidence: 99%
“…It has certain theoretical value for the design of new DMS. [14,20] showed that the doped system was relatively stable when Mn Zn was close to V O /V Zn . Therefore, the model with the closest Mn Zn to V Zn was selected in subsequent studies.…”
Section: Introductionmentioning
confidence: 99%